Erratum to “On the conical indentation response of elastic auxetic materials: Effects of Poisson's ratio, contact friction and cone angle” [Int. J. Solids Struct. 81 (2016) 33–42] - Photiou, Demetris; Sarris, Ernestos; Constantinides, Georgios (My University, 2017)
We regret to note that Eqs. (23) and (31) of (Photiou et al., 2016) contain a typographical error, introduced by mistyping the term “π/2” instead of the correct one “2/π”. Thus, Eqs. (23) and (31) of (Photiou et al., 2016) should read:[formula presented]Eq. (1) is consistent with the analytic solution of a rigid conical probe indenting a linear-elastic half-space, previously derived in the literature (see for example (Borodich, 2014; Love, 1939; Sneddon, 1965) and references therein) and extensively used thereafter (e.g., (Lim and Chaudhri, 2004; Vandamme et al., 2012)). We stress that all results and graphical data/figures presented in (Photiou et al., 2016) are correct and computed/plotted on the basis of the correct equations, Eqs. (1) and (2).The authors would like to thank Dr. M. Munawar Chaudhri from Cavendish Laboratory, Department of Physics, University of Cambridge for drawing this typographical error to their attention.
Keywords: Αuxetic materials; Structures; Solids